Struktur Komunitas Fitoplankton dan Tingkat Pencemaran di Danau Dendam Tak Sudah, Kota Bengkulu - Putri, Inten Diana (LPPM Universitas Terbuka, 2025)
Dendam Tak Sudah Lake (DDTS) is an aquatic ecosystem and nature reserve located in Dusun Besar Village, Singgaran Pati District, Bengkulu City. Its presence serves not only as a tourist destination and irrigation water supply for rice fields but also as a habitat for phytoplankton. The land use changes around the DDTS Nature Reserve have impacted the water quality of the lake, and phytoplankton are among the biota affected by these pressures. This study aims to assess the phytoplankton community structure and the pollution level in DDTS. The research was conducted by identifying and counting each phytoplankton species found and analyzing water quality. The results of the study showed that the phytoplankton richness in DDTS consisted of 20 species, including 8 species from the Bacillariophyceae class, 6 species from the Chlorophyceae class, 2 species from the Cyanophyceae class, and 4 species from the Euglenophyceae class. The highest phytoplankton abundance was found at the inlet with 1,135.2 individuals/l, followed by the midlet with 1,095.6 individuals/l, and the outlet with 997.2 individuals/l. The diversity index values were high (2.6-2.8), the evenness index was high (0.95-0.96), and dominance was low (0.07-0.08). The saprobic coefficient in DDTS was classified as β-Meso/Oligosaprobic, indicating that the water quality is lightly polluted, with a saprobic index value ranging from 0.6 to 0.87.